STRUKTUR, KOMPOSISI DAN PERTUMBUHAN PERMUDAAN ENDEMIK RAWA GAMBUT PADA LAHAN BEKAS KEBAKARAN DI STASIUN PENELITIAN ORANGUTAN TUANAN, KALIMANTAN TENGAH: Yudha1 dan Sri Suci Utami Atmoko 2 - JHT, Admin (Jurnal Hutan Tropika, 2018)
ABSTRACTThe aims of this study were to determine the composition, structure, and growth of endemicspecies of peat swamps in the areas of ex-burned, burned border, and non-burning areas; alsomeasured the growth of endemic seedlings in the burned area at the Orangutan Research Stationof Tuanan (SPOT); and also to know the type of orangutans feed tree in the Orangutan ResearchStation of Tuanan (SPOT). The location of this research is conducted in the area of ResearchStation of Orangutan Tuanan of Central Kalimantan Province on the ex-burned field, with theresearch period was 4 (four) months. The results showed that vegetation composition andstructure were dominated by plant species of Tutup Kabali (Diospyros pseudo-malabarica),Kayu Randa (Gardenia cf. Pterocalyx), Kumpang Daun Perak (Gymnacranthera sp.), ManggisHutan Daun Besar(Garcinia cf. Beccarii, Keput Bajuku (Stemonurus scorpioides, Tarantang(Campnosperma coriaceum), Karandau (Neoscortechinia sp.) dan Rambangun (Acronychiapedunculata).Based on the value of species diversity in the transect of SG and HR was lowmoderate and in transect SA and IS diversity was moderate-high. The fastest growth in SGtransect, where the average growth rate was 12.8 cm and 0.1 cm in diameter; whereas in the IStransect the growth was low, where the average growth rate was 1.5 cm and diameter 0.04 cm.Several dominant species of Orangutan feed plants in the research plots are Tutup Kabali(Diospyros pseudo-malabarica), Jelutung (Dyera polyphylla), Rambangun (Acronychiapedunculata), Bajuku Keput (Stemonurus scorpioides), Manggis Hutan Daun Besar (Garcinia cf.Beccari), Tarantang (Campnosperma coriaceum).Keywords: Composition, structure, growth, fire, orangutan feed.